Fe-based nanocrystal alloy magnetic core and method for manufacturing Fe-based nanocrystal alloy magnetic core

By using Fe-based nanocrystalline alloy strips with specific thickness and floor area ratio, combined with appropriate heating and magnetic field processing steps, the problem of low permeability of Fe-based nanocrystalline alloy cores in the high-frequency band domain is solved, and higher permeability and better high-frequency performance are achieved.

CN119864216APending Publication Date: 2025-04-22PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411436432.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-10-15
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, Fe-based nanocrystalline alloy core has a low permeability in the high frequency band domain, especially at 100 kHz, making it difficult to meet the needs of high efficiency and miniaturization.

Method used

The magnetic core was made by using a Fe-based nanocrystalline alloy tape with a thickness of 11 μm or more and less than 14 μm, and the tape's floor area ratio was controlled to be more than 73% during the magnetic core manufacturing process, and combined with appropriate heating and magnetic field processing steps.

Benefits of technology

The permeability of Fe-based nanocrystalline alloy core at a frequency of 100kHz is significantly improved, making it more suitable for high-frequency applications, and improving the performance and stability of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085126990000151
    Figure BDA0005085126990000151
  • Figure BDA0005085126990000171
    Figure BDA0005085126990000171
  • Figure BDA0005085126990000172
    Figure BDA0005085126990000172
Patent Text Reader

Abstract

The present invention addresses the problem of providing an Fe-based nanocrystal alloy magnetic core having a higher magnetic permeability than conventional magnetic cores, and a method for producing an Fe-based nanocrystal alloy magnetic core. [Solution] A Fe-based nanocrystal alloy magnetic core obtained by winding a Fe-based nanocrystal alloy strip, the Fe-based nanocrystal alloy strip having a thickness of 11 [mu] m or more and less than 14 [mu] m and a volume fraction of 73% or more as measured in accordance with IEC60404-8-11: 2018.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an Fe-based nanocrystalline alloy magnetic core and a method for manufacturing the Fe-based nanocrystalline alloy magnetic core. Background Art

[0002] With the electrification of automobiles and the increase in the frequency of semiconductors, the electronic devices used have become more efficient and smaller, which requires high-impedance materials that could not be achieved with conventional product sizes. In recent years, Fe-based nanocrystalline alloys have attracted much attention.

[0003] For example, Patent Document 1 describes an Fe-based nanocrystalline alloy magnetic core, which is a magnetic core obtained by winding an Fe-based nanocrystalline alloy strip, and the impedance relative permeability μrz of the magnetic core is greater than 90,000 at a frequency of 10 kHz, greater than 40,000 at a frequency of 100 kHz, and greater than 8,500 at a frequency of 1 MHz.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2015 / 190528 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] It is necessary to improve the magnetic permeability in the high frequency band, especially 100kHz.

[0009] An object of one embodiment of the present invention is to provide an Fe-based nanocrystalline alloy core having a higher magnetic permeability than conventional ones and a method for producing the Fe-based nanocrystalline alloy core.

[0010] Technical solutions for solving technical problems

[0011] <1>

[0012] A Fe-based nanocrystalline alloy magnetic core is a magnetic core obtained by winding a Fe-based nanocrystalline alloy strip, wherein the thickness of the Fe-based nanocrystalline alloy strip is greater than 11 μm and less than 14 μm, and the occupancy rate measured according to IEC60404-8-11:2018 is greater than 73%.

[0013] <2>

[0014] The Fe-based nanocrystalline alloy magnetic core as described in <1>, wherein one surface of the Fe-based nanocrystalline alloy strip is a roller surface and the other surface is a free surface, the maximum peak height Rp of the roller surface is greater than 1.2 μm, and the maximum valley depth Rv is less than 3.7 μm.

[0015] <3>

[0016] The Fe-based nanocrystalline alloy magnetic core as described in <2>, wherein the arithmetic mean roughness Ra of the roll surface of the Fe-based nanocrystalline alloy strip is 0.6 μm or less.

[0017] <4>

[0018] The Fe-based nanocrystalline alloy magnetic core as described in <2> or <3>, wherein the maximum cross-sectional height Rt of the roll surface of the Fe-based nanocrystalline alloy strip is 4 μm to 7 μm.

[0019] <5>

[0020] A method for manufacturing an Fe-based nanocrystalline alloy magnetic core, comprising: a step of winding an Fe-based amorphous alloy strip to make a magnetic core precursor; and a step of heating the magnetic core precursor.

[0021] The Fe-based amorphous alloy strip has a thickness of 11 μm or more and less than 14 μm, and an area ratio measured according to IEC60404-8-11:2018 is 73% or more.

[0022] <6>

[0023] A method for manufacturing an Fe-based nanocrystalline alloy magnetic core as described in <5>, wherein one surface of the Fe-based amorphous alloy strip is a roller surface, and the other surface is a free surface, the maximum peak height Rp of the roller surface is greater than 1.2 μm, and the maximum valley depth Rv is less than 3.7 μm.

[0024] <7>

[0025] The method for producing an Fe-based nanocrystalline alloy magnetic core as described in <6>, wherein the arithmetic mean roughness Ra of the roll surface of the Fe-based amorphous alloy strip is 0.6 μm or less.

[0026] <8>

[0027] The method for producing an Fe-based nanocrystalline alloy magnetic core as described in <6> or <7>, wherein the maximum cross-sectional height Rt of the roll surface of the Fe-based amorphous alloy strip is not less than 4 μm and not more than 7 μm.

[0028] <9>

[0029] The method for manufacturing an Fe-based nanocrystalline alloy magnetic core as described in any one of <5> to <8> further comprises the step of preparing the Fe-based amorphous alloy strip.

[0030] The process of manufacturing the Fe-based amorphous alloy strip includes: supplying a molten Fe-based alloy to a surface of a cooling roll; and spraying an atmospheric gas to the surface of the cooling roll to which the molten alloy is supplied.

[0031] Effects of the Invention

[0032] According to the present invention, there are provided an Fe-based nanocrystalline alloy magnetic core having a higher magnetic permeability than conventional ones and a method for producing the Fe-based nanocrystalline alloy magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic cross-sectional view showing an example of a production apparatus for producing an Fe-based amorphous alloy strip.

[0034] Figure 2 This is a diagram showing an example of a circular Fe-based nanocrystalline alloy core.

[0035] Figure 3 This is a diagram showing an example of an elliptical Fe-based nanocrystalline alloy core.

[0036] Figure 4 This is a diagram showing an example of a substantially quadrilateral Fe-based nanocrystalline alloy magnetic core.

[0037] Figure 5 This is a diagram showing heating conditions in the production of an Fe-based nanocrystalline alloy magnetic core.

[0038] 10: Melt nozzle

[0039] 20: Crucible

[0040] 30: Cooling roller

[0041] 40: High frequency coil

[0042] 50: Stripping gas nozzle

[0043] 60: Abrasive brush roller

[0044] 70: Atmosphere gas nozzle

[0045] 100: Alloy strip manufacturing device DETAILED DESCRIPTION

[0046] Hereinafter, the present invention will be described in detail.

[0047] In the present invention, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0048] In the present invention, in the numerical range recorded in stages, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.

[0049] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0050] In the present invention, the Fe-based nanocrystalline alloy strip refers to a strip (ribbon) containing an Fe-based nanocrystalline alloy.

[0051] In the present invention, the Fe-based nanocrystalline alloy refers to a nanocrystalline alloy in which Fe (iron) is the element with the largest content (atomic %) among the metal elements contained.

[0052] In the present invention, the Fe-based amorphous alloy strip refers to a strip (ribbon) containing an Fe-based amorphous alloy.

[0053] In the present invention, the Fe-based amorphous alloy refers to an amorphous alloy in which Fe (iron) is the largest element in content (atomic %) among the metal elements contained.

[0054] 〔Fe-based nanocrystalline alloy core〕

[0055] The Fe-based nanocrystalline alloy magnetic core of the present invention is a magnetic core obtained by winding a Fe-based nanocrystalline alloy strip having a thickness of 11 μm or more and less than 14 μm and an area ratio of 73% or more measured according to IEC60404-8-11:2018.

[0056] The Fe-based nano-crystalline alloy magnetic core of the present invention has a volume ratio of 73% or more of the Fe-based nano-crystalline alloy strip, and has a higher magnetic permeability than before.

[0057] Patent Document 1 does not describe focusing on the occupancy rate of the Fe-based nanocrystalline alloy strip.

[0058] (Fe-based nanocrystalline alloy strip)

[0059] The thickness of the Fe-based nanocrystalline alloy strip is 11 μm or more and less than 14 μm, preferably 11 μm to 12 μm.

[0060] Since the thickness of the Fe-based nanocrystalline alloy ribbon is 11 μm or more, the Fe-based nanocrystalline alloy ribbon is less likely to break during winding of the magnetic core, and can be wound continuously.

[0061] Since the thickness of the Fe-based nanocrystalline alloy strip is less than 14 μm, the current loss is small and the magnetic permeability of the Fe-based nanocrystalline alloy magnetic core is high.

[0062] The thickness of the Fe-based nanocrystalline alloy ribbon is measured by the following method.

[0063] It can be calculated according to IEC 60404-8-11:2018 from the mass, length, width and density of a 2000 mm long strip collected from the casting direction.

[0064] The area ratio of the Fe-based nanocrystalline alloy strip is 73% or more, preferably 75% or more. The upper limit of the area ratio is not particularly limited, and is, for example, 77%.

[0065] Since the area ratio of the Fe-based nanocrystalline alloy ribbon is 73% or more, the magnetic permeability of the Fe-based nanocrystalline alloy magnetic core is high.

[0066] The occupancy rate of the Fe-based nanocrystalline alloy ribbon is measured by the following method.

[0067] First, the mass, outer diameter, inner diameter, and height of the Fe-based nanocrystalline alloy core were measured.

[0068] The volume of the Fe-based nanocrystalline alloy core is calculated from the outer diameter, inner diameter and height. The occupancy rate is calculated according to the following formula using the mass and volume of the Fe-based nanocrystalline alloy core and the density of the Fe-based nanocrystalline alloy ribbon.

[0069] Occupancy rate (%) = mass ÷ (volume × density)

[0070] The Fe-based nanocrystalline alloy strip preferably has a width dimension of 30 mm to 300 mm.

[0071] The Fe-based nano-crystalline alloy strip is preferably formed in a manner that a surface that contacts with the chill roll during manufacture is the roll surface, and another surface that does not contact with the chill roll is the free surface. The roll surface and the free surface can be judged by visual inspection by the gloss on the surface of the Fe-based nano-crystalline alloy strip. The roll surface lacks gloss than the free surface because the concavo-convex of the chill roll surface has been transferred. Therefore, in the two faces of the Fe-based nano-crystalline alloy strip, the face with gloss is the free surface by comparison, and the face without gloss is the roll surface.

[0072] The Fe-based nanocrystalline alloy strip preferably has an arithmetic mean roughness Ra of 0.6 μm or less on the roll surface, and more preferably 0.1 μm to 0.6 μm. By setting the arithmetic mean roughness Ra of the roll surface of the Fe-based nanocrystalline alloy strip to 0.6 μm or less, an Fe-based nanocrystalline alloy strip having a small surface irregularity on the roll surface can be obtained.

[0073] It should be noted that the arithmetic mean roughness Ra is measured according to JIS B 0601:2001 with the evaluation length set to 4.0 mm, the cutoff value set to 0.8 mm, and the cutoff type set to 2RC (phase compensation). The evaluation length direction is measured along the width direction at the center of the width direction (direction orthogonal to the casting direction) of the Fe-based nanocrystalline alloy strip. In addition, the Fe-based nanocrystalline alloy strip has a tendency to have a larger arithmetic mean roughness Ra on the roll surface than on the free surface.

[0074] The maximum cross-sectional height Rt of the roll surface of the Fe-based nanocrystalline alloy strip is preferably 4 μm to 7 μm. By setting the maximum cross-sectional height Rt of the roll surface of the Fe-based nanocrystalline alloy strip to be greater than 4 μm, it can be expected that the insulation performance between the Fe-based nanocrystalline alloy strips will be improved and the magnetic properties will be improved when the magnetic core is wound. By setting the maximum cross-sectional height Rt of the roll surface of the Fe-based nanocrystalline alloy strip to be less than 7 μm, it is possible to produce an Fe-based nanocrystalline alloy strip with less surface unevenness on the roll surface, and the occupancy rate is improved.

[0075] The maximum cross-sectional height Rt was measured (evaluated) according to JIS B 0601:2001 with the evaluation length set to 4.0 mm, the cutoff value set to 0.8 mm, and the cutoff type set to 2RC (phase compensation). The evaluation length was measured along the width direction at the center of the width direction (direction orthogonal to the casting direction) of the Fe-based nanocrystalline alloy strip.

[0076] The maximum peak height Rp of the roll surface of the Fe-based nanocrystalline alloy strip is preferably 1.2 μm or more, and more preferably 1.2 μm to 2.0 μm. By setting the maximum peak height Rp of the roll surface of the Fe-based nanocrystalline alloy strip to 1.2 μm or more, it is expected that the insulation performance between the Fe-based nanocrystalline alloy strips will be improved when the magnetic core is wound, and the magnetic properties will be improved.

[0077] The maximum peak height Rp was measured (evaluated) according to JIS B 0601:2001, with the evaluation length set to 4.0 mm, the cutoff value set to 0.8 mm, and the cutoff type set to 2RC (phase compensation). The evaluation length was measured along the width direction at the center of the width direction (direction orthogonal to the casting direction) of the Fe-based nanocrystalline alloy strip.

[0078] The maximum valley depth Rv of the roll surface of the Fe-based nanocrystalline alloy strip is preferably 3.7 μm or less, and more preferably 0.5 μm to 3.7 μm. By setting the maximum valley depth Rv of the roll surface of the Fe-based nanocrystalline alloy strip to 3.7 μm or less, it is possible to produce an Fe-based nanocrystalline alloy strip with less surface irregularities on the roll surface, and the occupancy rate is improved.

[0079] The maximum valley depth Rv was measured (evaluated) according to JIS B 0601:2001, with the evaluation length set to 4.0 mm, the cutoff value set to 0.8 mm, and the cutoff type set to 2RC (phase compensation). The evaluation length was measured along the width direction at the center of the width direction (direction orthogonal to the casting direction) of the Fe-based nanocrystalline alloy strip.

[0080] The maximum height Rz of the roller surface of the Fe-based nanocrystalline alloy strip is preferably 3.0 μm to 5.0 μm. By setting the maximum height Rz of the roller surface of the Fe-based nanocrystalline alloy strip to be greater than 3.0 μm, it can be expected that the insulation performance between the Fe-based nanocrystalline alloy strips will be improved when winding the magnetic core, and the magnetic properties will be improved. By setting the maximum height Rz of the roller surface of the Fe-based nanocrystalline alloy strip to be less than 5.0 μm, it is possible to produce an Fe-based nanocrystalline alloy strip with less surface unevenness on the roller surface, and the occupancy rate is improved.

[0081] The maximum height Rz is measured (evaluated) according to JIS B 0601:2001, with the evaluation length set to 4.0 mm, the cutoff value set to 0.8 mm, and the cutoff type set to 2RC (phase compensation). The evaluation length direction is measured along the width direction at the center of the width direction (direction orthogonal to the casting direction) of the Fe-based nanocrystalline alloy strip.

[0082] The Fe-based nanocrystalline alloy constituting the Fe-based nanocrystalline alloy ribbon preferably has Fe (iron) as the element with the largest content (atomic %) among the metal elements contained therein, and preferably has a Fe—Si—B—Cu—Nb composition.

[0083] The Fe-based nanocrystalline alloy contains at least Fe (iron), preferably further contains Si (silicon) and B (boron), and more preferably contains copper (Cu) and niobium (Nb) in addition to Fe, Si and B.

[0084] The Fe-based nanocrystalline alloy may further contain C (carbon).

[0085] Furthermore, niobium (Nb) may be replaced with molybdenum (Mo) or vanadium (V), and part of iron (Fe) may be replaced with nickel (Ni) or cobalt (Co).

[0086] As an Fe-based nanocrystalline alloy, for example, the following Fe-based nanocrystalline alloy can be listed: when the total content of Fe, Si, B, Cu, Nb, C and inevitable impurities is set to 100 atomic %, the Fe content is 72 atomic % to 84 atomic %, the Si content is 2 atomic % to 20 atomic %, the B content is 5 atomic % to 14 atomic %, the Cu content is 0.2 atomic % to 2 atomic %, the Nb content is 0.1 atomic % to 5 atomic %, the C (carbon) content is less than 0.5 atomic %, and the remainder contains impurities.

[0087] When the Fe content is 72 atomic % or more, the saturation magnetic flux density of the alloy strip becomes higher, so the increase in size or weight of the magnetic core manufactured using the alloy strip is further suppressed. When the Fe content is 84 atomic % or less, the decrease in the Curie point and the crystallization temperature of the alloy are further suppressed, so the stability of the magnetic properties of the magnetic core is further improved.

[0088] In addition, when the C (carbon) content is 0.5 atomic % or less, the embrittlement of the alloy strip is further suppressed. The C (carbon) content is preferably 0.1 atomic % to 0.5 atomic %. A more preferred C (carbon) content is 0.15 atomic % to 0.35 atomic %.

[0089] When the above-mentioned C (carbon) content is 0.1 atomic % or more, the productivity of the molten alloy and the alloy ribbon is excellent.

[0090] More preferably, the Fe-based amorphous alloy is as follows: when the total content of Fe, Si, B, Cu, Nb, C and inevitable impurities is set to 100 atomic %, the content of Si is 12 atomic % to 18 atomic %, the content of B is 5 atomic % to 10 atomic %, the content of Cu is 0.8 atomic % to 1.2 atomic %, the content of Nb is 2.0 atomic % to 4.0 atomic %, the content of C is 0.1 atomic % to 0.5 atomic %, and the remainder contains Fe and inevitable impurities. More preferably, the Fe-based amorphous alloy is as follows: when the total content of Fe, Si, B, Cu, Nb, C and inevitable impurities is set to 100 atomic %, the content of Si is 14 atomic % to 16 atomic %, the content of B is 6 atomic % to 9 atomic %, the content of Cu is 0.9 atomic % to 1.1 atomic %, the content of Nb is 2.5 atomic % to 3.5 atomic %, the content of C is 0.15 atomic % to 0.35 atomic %, and the remainder contains Fe and inevitable impurities.

[0091] In each of the above-mentioned Fe-based amorphous alloys, when the total content of Fe, Si and B is set to 100 atomic %, the content of C (carbon) is preferably 0.1 atomic % to 0.5 atomic %.

[0092] (Magnetic Permeability)

[0093] The Fe-based nanocrystalline alloy core of the present invention preferably has a magnetic permeability of 32,000 or more at a frequency of 100 kHz, more preferably 36,000 or more, and even more preferably 40,000 or more. The upper limit of the magnetic permeability is, for example, 47,000.

[0094] The magnetic permeability mentioned here means the real part μr′ of the complex magnetic permeability.

[0095] The magnetic permeability is calculated by the following method.

[0096] μr′=((OD+ID)×π×L) / (μ0×(OD-ID)×H×PF×N 2 )

[0097] OD: Outer Diameter

[0098] ID: inner diameter

[0099] μ0: Magnetic permeability in vacuum = 4π×10 -7

[0100] f: frequency

[0101] PF: Plot ratio

[0102] H: Height

[0103] L: Inductance

[0104] N: Number of turns when L is measured (1 turn)

[0105] Figure 2 This is a diagram showing an example of a circular Fe-based nanocrystalline alloy core.

[0106] exist Figure 2 In the figure, OD stands for outer diameter and ID stands for inner diameter.

[0107] The Fe-based nanocrystalline alloy magnetic core of the present invention has a high magnetic permeability at a frequency of 100 kHz and can suppress noise when mounted on electrical / electronic equipment.

[0108] The shape of the Fe-based nanocrystalline alloy core of the present invention is not particularly limited, and examples thereof include a circular shape, an elliptical shape, and a substantially quadrilateral shape.

[0109] Figure 3 This is a diagram showing an example of an elliptical Fe-based nanocrystalline alloy core.

[0110] In the case where the Fe-based nanocrystalline alloy magnetic core is elliptical, the magnetic permeability is calculated by the following method.

[0111] First, calculate the average magnetic path length and effective cross-sectional area.

[0112] Le: Average magnetic path length = 2(C-A)+π(A+B) / 2

[0113] Ae: Effective cross-sectional area = {(A-B) × H × PF} / 2

[0114] μr′=(Le×L) / (μ0×Ae×N 2 )

[0115] A: The narrower width of the oval's outer circumference

[0116] B: The narrower width of the inner circumference of the oval

[0117] C: The wider width of the outer circumference of the oval

[0118] Figure 4 This is a diagram showing an example of a substantially quadrilateral Fe-based nanocrystalline alloy magnetic core.

[0119] When the Fe-based nanocrystalline alloy core is substantially quadrilateral, the magnetic permeability is calculated by the following method.

[0120] First, calculate the average magnetic path length and effective cross-sectional area.

[0121] Le: Average magnetic path length = (D-2R) + (E-2R) + π (R + R')

[0122] Ae: Effective cross-sectional area = {(D-F) × H × PF} / 2

[0123] μr′=(Le×L) / (μ0×Ae×N 2 )

[0124] D: The wider width of the outer circumference of a roughly quadrilateral

[0125] E: The narrower width of the outer periphery of a roughly quadrilateral

[0126] F: The wider width of the inner circumference of a roughly quadrilateral

[0127] R: The curvature of the corners of the outer periphery of a roughly quadrilateral

[0128] R': The curvature of the inner corner of the roughly quadrilateral

[0129] The Fe-based nanocrystalline alloy core of the present invention is suitable for pulse power magnetic components used in common mode choke coils, inductors, various transformers, laser power supplies, accelerators, etc. These are obtained by winding a coil on the Fe-based nanocrystalline alloy core of the present invention.

[0130] [Method for producing Fe-based nanocrystalline alloy magnetic core]

[0131] The method for manufacturing an Fe-based nanocrystalline alloy magnetic core of the present invention comprises: a step of winding an Fe-based amorphous alloy strip to manufacture a magnetic core precursor; and a step of heating the magnetic core precursor.

[0132] (Making process of magnetic core precursor)

[0133] The magnetic core precursor manufacturing step is a step of winding a Fe-based amorphous alloy ribbon to manufacture a magnetic core precursor.

[0134] The Fe-based amorphous alloy strip has a thickness of 11 μm or more and less than 14 μm, and an area ratio measured in accordance with IEC60404-8-11:2018 is 73% or more.

[0135] The preferred manner of the thickness and the area ratio of the Fe-based amorphous alloy strip is the same as the preferred manner of the thickness and the area ratio of the Fe-based nanocrystalline alloy strip.

[0136] The method for measuring the thickness and the area ratio of the Fe-based amorphous alloy strip is the same as the method for measuring the thickness and the area ratio of the Fe-based nanocrystalline alloy strip.

[0137] The preferred composition of the Fe-based amorphous alloy strip is the same as the preferred composition of the Fe-based nanocrystalline alloy strip.

[0138] The Fe-based amorphous alloy strip preferably has one surface as a roll surface and the other surface as a free surface. The preferred form of the roll surface properties of the Fe-based amorphous alloy strip is the same as the preferred form of the roll surface properties of the Fe-based nanocrystalline alloy strip.

[0139] (Heating step of magnetic core precursor)

[0140] The step of heating the magnetic core precursor is a step of heating the magnetic core precursor.

[0141] In order to crystallize the Fe-based amorphous alloy to form the Fe-based nanocrystalline alloy, it is preferable to heat at a temperature higher than the crystallization start temperature of the Fe-based amorphous alloy.

[0142] Specifically, the highest temperature in the heating step is preferably a temperature higher than the crystallization start temperature of the Fe-based amorphous alloy by 60° C. or more.

[0143] The crystallization start temperature is determined by differential scanning calorimetry. It is difficult to accurately determine the true crystallization start temperature, and identification using differential scanning calorimetry (DSC) is effective. The temperature at which the exothermic reaction caused by the start of nanocrystallization is detected during heating is taken as the crystallization start temperature. The crystallization start temperature is measured at a heating rate of 10°C / min.

[0144] In the heating step, a magnetic field is preferably applied in the height direction of the magnetic core precursor.

[0145] The intensity of the applied magnetic field is preferably 50 kA / m to 300 kA / m, more preferably 60 kA / m to 280 kA / m.

[0146] The method for manufacturing the Fe-based nanocrystalline alloy magnetic core of the present invention may include a step of manufacturing a Fe-based amorphous alloy strip.

[0147] (Fe-based amorphous alloy strip production process)

[0148] Reference Figure 1 A method for producing a Fe-based amorphous alloy strip will be described.

[0149] Figure 1 1 is a schematic cross-sectional view showing an example of a manufacturing apparatus for manufacturing an Fe-based amorphous alloy strip. The cross-sectional view when the alloy strip manufacturing apparatus is cut at a plane perpendicular to the axial direction of the cooling roller 30 and the width direction of the alloy strip is shown. Among them, the alloy strip 22C is an example of an Fe-based amorphous alloy strip according to an embodiment of the present invention. In addition, the axial direction of the cooling roller 30 and the width direction of the alloy strip 22C are the same direction.

[0150] like Figure 1 As shown, the alloy strip manufacturing apparatus 100 includes a crucible 20 having a melt nozzle 10 , and a cooling roller 30 whose outer peripheral surface faces the front end of the melt nozzle 10 .

[0151] The crucible 20 has an internal space capable of containing molten alloy 22A as a raw material of the alloy strip 22C, and the internal space is connected to the molten metal flow path in the molten metal nozzle 10. Thus, the molten alloy 22A (molten metal 22A) contained in the crucible 20 can be discharged to the cooling roller 30 through the molten metal nozzle 10. Figure 1 , the discharge direction and flow direction of the molten alloy 22A are indicated by arrow Q). The crucible 20 and the melt nozzle 10 may be integrally formed or may be formed as separate bodies.

[0152] A high frequency coil 40 as a heating unit is disposed at least partially around the crucible 20. Thus, the crucible 20 containing the mother alloy of the alloy strip can be heated to generate the molten alloy 22A in the crucible 20, and the molten alloy 22A supplied to the crucible 20 from the outside can be maintained in a liquid state.

[0153] The molten alloy nozzle 10 has an opening (discharge port) for discharging the molten alloy in the direction of arrow Q. The opening is preferably a rectangular (slit-shaped) opening.

[0154] The distance (closest distance) between the tip of the melt nozzle 10 and the outer peripheral surface of the cooling roller 30 is close enough to form a molten pool 22B (Puddle) when the molten alloy 22A is discharged through the melt nozzle 10 .

[0155] The cooling roller 30 is axially rotated in the direction of rotation P. A cooling medium such as water is circulated inside the cooling roller 30 to cool the coating film of the molten alloy formed on the outer peripheral surface of the cooling roller 30. By cooling the coating film of the molten alloy, an alloy strip 22C (Fe-based amorphous alloy strip) is generated.

[0156] As the material of the cooling roller 30, Cu and Cu alloys (Cu-Be alloy, Cu-Cr alloy, Cu-Zr alloy, Cu-Cr-Zr alloy, Cu-Ni alloy, Cu-Ni-Si alloy, Cu-Ni-Si-Cr alloy, Cu-Zn alloy, Cu-Sn alloy, Cu-Ti alloy, etc.) can be listed. In terms of high thermal conductivity, Cu alloy is preferred, and Cu-Be alloy, Cu-Cr-Zr alloy, Cu-Ni alloy, Cu-Ni-Si alloy, or Cu-Ni-Si-Cr alloy is more preferred.

[0157] The surface roughness of the outer peripheral surface of the cooling roller 30 is not particularly limited. The arithmetic mean roughness (Ra) of the outer peripheral surface of the cooling roller 30 is preferably 0.1 μm to 0.5 μm, and more preferably 0.1 μm to 0.3 μm. When the arithmetic mean roughness Ra of the outer peripheral surface of the cooling roller 30 is less than 0.5 μm, the occupancy rate when the alloy strip is used to manufacture the wound magnetic core is further improved. If the arithmetic mean roughness Ra of the outer peripheral surface of the cooling roller 30 is greater than 0.1 μm, it is easier to adjust Ra.

[0158] From the viewpoint of cooling performance, the diameter of the cooling roller 30 is preferably 200 mm to 1000 mm, and more preferably 300 mm to 800 mm. In addition, the rotation speed of the cooling roller 30 can be set to the range usually set in the single roll method, and the peripheral speed is preferably 10 m / s to 40 m / s, and more preferably 20 m / s to 30 m / s.

[0159] The alloy strip manufacturing apparatus 100 further includes a stripping gas nozzle 50 as a stripping unit for stripping the Fe-based amorphous alloy strip from the outer peripheral surface of the cooling roller 30 on the downstream side (hereinafter, also referred to as the "downstream side") of the melt nozzle 10 in the rotation direction of the cooling roller 30. In one example of the present invention, the stripping gas nozzle 50 is directed in the direction opposite to the rotation direction P of the cooling roller 30 ( Figure 1 The stripping gas is blown in the direction of the dotted arrow in the figure to strip the alloy strip 22C from the cooling roller 30. As the stripping gas, for example, a high-pressure gas such as nitrogen or compressed air can be used.

[0160] The alloy strip manufacturing device 100 also has a grinding brush roller 60 as a grinding unit for grinding the outer peripheral surface of the cooling roller 30 at a position downstream of the stripping gas nozzle 50. The grinding brush roller 60 includes a roller shaft member 61 and a grinding brush 62 arranged around the roller shaft member 61. The grinding brush 62 is composed of a non-woven fabric coated with a plurality of abrasive grains. The grinding brush roller 60 is axially rotated in the direction of the rotation direction R, and the outer peripheral surface of the cooling roller 30 is ground by the non-woven fabric of the grinding brush 62.

[0161] The purpose of grinding by the grinding unit (eg, grinding brush roller 60) is not necessarily limited to cutting the outer peripheral surface of the cooling roller, but also includes removing the residues remaining on the outer peripheral surface of the cooling roller. The purpose of grinding is preferably at least one of the first purpose and the second purpose described below.

[0162] The first purpose is to repair the deterioration of the smoothness of the outer surface of the cooling roller. In detail, when the molten alloy first contacts the outer surface of the cooling roller, a very small part of the outer surface of the cooling roller (for example, the Cu alloy) dissolves in the molten alloy, forming tiny recesses (detached portions) on the outer surface of the cooling roller, which sometimes deteriorates the smoothness of the outer surface of the cooling roller. The deterioration of the smoothness of the outer surface of the cooling roller will cause the deterioration of the smoothness of the roller surface (the surface in contact with the outer surface of the cooling roller. The same below) of the manufactured alloy strip. In the case where the smoothness of the outer surface of the cooling roller deteriorates, the portions that are convex relative to the above-mentioned tiny recesses (detached portions) (that is, the portions where dissolution is suppressed) are basically evenly removed by the above-mentioned grinding, thereby also repairing the deterioration of the smoothness of the outer surface of the cooling roller. As a result, the deterioration of the smoothness of the roller surface of the alloy strip caused by the deterioration of the smoothness of the outer surface of the cooling roller can be suppressed.

[0163] The second purpose is to remove the residue (alloy) remaining on the outer surface of the cooling roller after the alloy strip is peeled off. The molten alloy discharged to the outer surface of the cooling roller is rapidly cooled to form an alloy strip, and then peeled off from the outer surface of the cooling roller. At this time, sometimes a part of the alloy that is the material of the alloy strip is not peeled off from the outer surface of the cooling roller and remains as residue, and the residue is fixedly attached to the outer surface of the cooling roller to form a convex portion. The casting of the alloy strip is continuously carried out, so the molten alloy is discharged again for the outer surface of the cooling roller where the convex portion is formed by the above-mentioned residue. As a result, in the roller surface of the manufactured alloy strip, a concave portion is formed at a position corresponding to the above-mentioned convex portion, and sometimes the smoothness of the roller surface of the alloy strip is deteriorated. In addition, when the thermal conductivity of the residue (alloy) constituting the above-mentioned convex portion is lower than the thermal conductivity of the outer surface of the cooling roller (for example, Cu alloy), in the above-mentioned convex portion, the rapid cooling characteristics brought by the cooling roller are locally deteriorated, and the magnetic properties of the alloy strip may be reduced. In the case where the above-mentioned residue remains on the outer peripheral surface of the cooling roller after the alloy strip is peeled, the above-mentioned residue can also be removed by the above-mentioned grinding. As a result, the deterioration of the smoothness of the roller surface of the alloy strip caused by the above-mentioned residue can be suppressed. In addition, the reduction of the magnetic properties of the alloy strip caused by the above-mentioned residue can be suppressed.

[0164] The alloy strip manufacturing apparatus 100 further includes an atmospheric gas nozzle 70 for spraying (supplying) an atmospheric gas toward the surface of the cooling roller to which the molten alloy is supplied.

[0165] As for the atmospheric gas ejected from the atmospheric gas nozzle 70 , carbon dioxide gas or carbon monoxide gas is ejected in order to control the gas atmosphere near the roller surface at the tip of the nozzle.

[0166] The alloy strip manufacturing apparatus 100 may include other elements (for example, a winding roll for winding the manufactured alloy strip 22C, etc.) in addition to the above-mentioned elements.

[0167] Next, an example of a method for manufacturing an alloy strip 22C using the alloy strip manufacturing apparatus 100 is described. First, a molten alloy 22A serving as a raw material for the alloy strip 22C is prepared in the crucible 20. The temperature of the molten alloy 22A can be appropriately set in consideration of the composition of the alloy, for example, 1210°C to 1410°C, preferably 1280°C to 1400°C.

[0168] Next, the molten alloy is discharged through the melt nozzle 10 toward the outer peripheral surface of the cooling roller 30 rotating axially in the rotation direction P, and a coating film of the molten alloy is formed while forming a molten pool 22B. The formed coating film is cooled on the outer peripheral surface of the cooling roller 30, and an alloy strip 22C is formed on the outer peripheral surface. Then, the alloy strip 22C formed on the outer peripheral surface of the cooling roller 30 is stripped from the outer peripheral surface of the cooling roller 30 by spraying a stripping gas from the stripping gas nozzle 50, and is wound into a roll by a winding roller (not shown) and recovered. On the other hand, the outer peripheral surface of the cooling roller 30 after stripping the alloy strip 22C is ground by the grinding brush 62 of the grinding brush roller 60 rotating axially in the rotation direction R. The molten alloy is discharged again from the outer peripheral surface of the cooling roller 30 after grinding. By repeating the above actions, the long strip of alloy strip 22C is continuously manufactured (cast).

[0169] The method for producing the Fe-based nanocrystalline alloy magnetic core of the present invention may further include a step of impregnating the magnetic core with an epoxy resin diluted with an organic solvent after the step of heating the magnetic core precursor. After the impregnation, it is preferably dried.

[0170] Example

[0171] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.

[0172] <Production of Fe-based amorphous alloy strip>

[0173] Prepare and Figure 1 The alloy strip manufacturing apparatus 100 shown in the figure is the same as the alloy strip manufacturing apparatus 100. As the cooling roll, a cooling roll having an outer peripheral surface made of Cu-Be alloy, a diameter of 400 mm, and an outer peripheral surface arithmetic mean roughness Ra of 0.3 μm was used.

[0174] First, a molten alloy composed of Fe, Si, B, Cu, Nb, C and inevitable impurities (hereinafter also referred to as "Fe-Si-B-Cu-Nb molten alloy") is prepared in a crucible. Specifically, pure iron, ferrosilicon and ferroboron are mixed and dissolved to prepare a molten alloy, wherein when the total content of Fe, Si, B, Cu, Nb, C and inevitable impurities is set to 100 atomic %, the content of Si is 15 atomic %, the content of B is 7 atomic %, the content of Cu is 1 atomic %, the content of Nb is 3 atomic %, the content of C is 0.2 atomic %, and the remainder is composed of Fe and inevitable impurities. The atomic % value is the amount obtained by collecting a part of the alloy from the melt and measuring it by ICP emission spectrometry.

[0175] Next, the Fe-Si-B-Cu-Nb molten alloy was discharged from the opening of the molten metal nozzle having a rectangular (slit-shaped) opening with a long side length of 53 mm × a short side length of 0.3 mm to the outer peripheral surface of the rotating cooling roller, and was rapidly solidified to produce (cast) 500 kg of amorphous alloy strip with a width of 53 mm. The casting time was 60 minutes, and the alloy strip was continuously cast. The above casting was performed while grinding the outer peripheral surface of the cooling roller with the grinding brush (non-woven fabric) of the grinding brush roller.

[0176] The detailed conditions of casting are shown below.

[0177] <Casting conditions>

[0178] Molten alloy temperature: 1350℃~1390℃

[0179] Circumferential speed of cooling roller: 20m / s~30m / s

[0180] Molten alloy discharge pressure: Adjustable within the range of 5kPa to 30kPa

[0181] Distance (gap) between the tip of the melt nozzle and the outer surface of the cooling roller: Adjustable within the range of 0.1mm to 0.35mm

[0182] <Fabrication of Fe-based Nanocrystalline Alloy Magnetic Core>

[0183] The obtained Fe-based amorphous alloy strip is wound to produce a magnetic core precursor. Figure 5 The Fe-based nanocrystalline alloy magnetic core was produced by heating according to the temperature profile shown.

[0184] Specifically, the sample was kept at 25°C for 5 minutes, heated to 430°C in 40 minutes, heated to 580°C in 10 minutes, kept at 580°C for 10 minutes, and cooled to 300°C in 1 hour. In addition, a magnetic field of 80 kA / m was applied within the range of 520°C to 580°C for 30 minutes.

[0185] In Example 1 and Comparative Example 1, the tension applied to the Fe-based amorphous alloy strip was adjusted so that the occupancy ratios became the values ​​shown in Table 1.

[0186] The magnetic permeability of the produced Fe-based nanocrystalline alloy core was measured. The measurement results are shown in Table 1.

[0187] [Table 1]

[0188]

[0189] As shown in Table 1, Example 1 is a magnetic core formed by winding an Fe-based nanocrystalline alloy strip, the thickness of the Fe-based nanocrystalline alloy strip is greater than 11 μm and less than 14 μm, and the occupancy rate measured according to IEC60404-8-11:2018 is greater than 73%, so the magnetic permeability is higher than that of Comparative Example 1.

[0190] In Example 1, the magnetic permeability is 32,000 or more at a frequency of 100 kHz.

[0191] <Example 100>

[0192] Next, the Fe-based amorphous alloy strip is used to produce a circular Fe-based nanocrystalline alloy magnetic core.

[0193] The outer diameter, inner diameter, height and weight are shown in Table 2. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz.

[0194] [Table 2]

[0195] Outer diameter [mm] Inner diameter [mm] Height [mm] Weight [g] Magnetic Permeability 27.28 20.77 10 13.56 36516 27.24 20.78 10 13.86 36360 27.16 20.79 10 13.79 35701 40.9 30.7 30 89.3 37066 31.27 21.05 15 34.63 35652 31.52 20.8 15 35.79 36123 31.5 20.82 15 35.36 36645

[0196] <Example 200>

[0197] A circular Fe-based nanocrystalline alloy core was produced by the same method as in Example 100 except that the impregnation step was performed after the heating step of the core precursor.

[0198] In the impregnation step, the heated magnetic core is impregnated with epoxy resin diluted with acetone.

[0199] The outer diameter, inner diameter, height and weight are shown in Table 3. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz.

[0200] [Table 3]

[0201] Outer diameter [mm] Inner diameter [mm] Height [mm] Weight [g] Magnetic Permeability 27.19 20.78 10 13.52 36024 27.28 20.74 10 14.09 37567 59.57 48.41 30 158.72 35971 31.46 20.69 15 35.27 35577 31.47 20.79 15 35.25 36145 31.48 20.76 15 35.21 36711

[0202] <Example 300>

[0203] After making a circular Fe-based nanocrystalline alloy core, it is molded and made Figure 3 The elliptical Fe-based nanocrystalline alloy magnetic core shown.

[0204] The outer diameter, inner diameter, height and weight before molding are shown in Table 4. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz.

[0205] In Table 4, A after molding refers to the narrower width in the outer circumference of the ellipse, and B after molding refers to the narrower width in the inner circumference of the ellipse.

[0206] [Table 4]

[0207]

[0208] <Example 400>

[0209] After the circular Fe-based nanocrystalline alloy core is made, it is molded and made Figure 4 The substantially quadrilateral Fe-based nanocrystalline alloy magnetic core shown.

[0210] The outer diameter, inner diameter, height and weight before molding are shown in Table 5. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz.

[0211] In Table 5, D after molding refers to the wider width in the outer periphery of the roughly quadrilateral, E after molding refers to the narrower width in the outer periphery of the roughly quadrilateral, F after molding refers to the wider width in the inner periphery of the roughly quadrilateral, and G after molding refers to the narrower width in the inner periphery of the roughly quadrilateral.

[0212] [Table 5]

[0213]

[0214] According to Examples 100 to 400, it is possible to obtain Fe-based nanocrystalline alloy cores of various shapes having a magnetic permeability of 32,000 or more at 100 kHz.

Claims

1. An Fe-based nanocrystalline alloy magnetic core, which is a magnetic core obtained by winding a Fe-based nanocrystalline alloy strip, wherein the Fe-based nanocrystalline alloy magnetic core is characterized in that: The Fe-based nanocrystalline alloy strip has a thickness of 11 μm or more and less than 14 μm, and an area ratio measured according to IEC60404-8-11:2018 is 73% or more.

2. The Fe-based nanocrystalline alloy magnetic core according to claim 1, characterized in that: One surface of the Fe-based nanocrystalline alloy strip is a roll surface, and the other surface is a free surface. The maximum peak height Rp of the roller surface is 1.2 μm or more, and the maximum valley depth Rv is 3.7 μm or less.

3. The Fe-based nanocrystalline alloy magnetic core according to claim 2, characterized in that: The arithmetic mean roughness Ra of the roll surface of the Fe-based nanocrystalline alloy strip is 0.6 μm or less.

4. The Fe-based nanocrystalline alloy magnetic core according to claim 2, characterized in that: The maximum cross-sectional height Rt of the roll surface of the Fe-based nanocrystalline alloy strip is 4 μm or more and 7 μm or less.

5. A method for manufacturing a Fe-based nanocrystalline alloy magnetic core, characterized in that: include: A process of winding a Fe-based amorphous alloy strip to produce a magnetic core precursor; and a step of heating the magnetic core precursor, The Fe-based amorphous alloy strip has a thickness of 11 μm or more and less than 14 μm, and an area ratio measured according to IEC60404-8-11:2018 is 73% or more.

6. The method for manufacturing the Fe-based nanocrystalline alloy magnetic core according to claim 5, characterized in that: One surface of the Fe-based amorphous alloy strip is a roll surface, and the other surface is a free surface. The maximum peak height Rp of the roller surface is 1.2 μm or more, and the maximum valley depth Rv is 3.7 μm or less.

7. The method for manufacturing a Fe-based nanocrystalline alloy magnetic core according to claim 6, characterized in that: The arithmetic mean roughness Ra of the roll surface of the Fe-based amorphous alloy strip is 0.6 μm or less.

8. The method for manufacturing a Fe-based nanocrystalline alloy magnetic core according to claim 6, characterized in that: The maximum cross-sectional height Rt of the roller surface of the Fe-based amorphous alloy strip is 4 μm to 7 μm.

9. A method for manufacturing an Fe-based nanocrystalline alloy magnetic core, which is used to manufacture the Fe-based nanocrystalline alloy magnetic core according to any one of claims 5 to 8, wherein the manufacturing method is characterized in that: The method also includes a step of manufacturing the Fe-based amorphous alloy strip. The process of making the Fe-based amorphous alloy strip comprises: a step of supplying a molten alloy of an Fe-based alloy to a surface of a cooling roll; and A step of spraying an atmospheric gas onto a surface of the cooling roller to which the molten alloy is supplied.

Citation Information

Patent Citations

  • Fe-BASED NANOCRYSTALLINE ALLOY CORE AND METHOD FOR PRODUCING Fe-BASED NANOCRYSTALLINE ALLOY CORE

    WO2015190528A1